ARTIFICIAL INTELLIGENCE IN EARLY DISEASE DETECTION: REVOLUTIONIZING DIAGNOSTIC PRACTICES IN MEDICINE - Safiullah Aziz; Shazia Akhtar; Chen Mei (Journal of World Future Medicine, Health and Nursing, 2026)
The integration of Artificial Intelligence (AI) in medicine has the potential to revolutionize early disease detection, improving diagnostic practices and patient outcomes. Early detection of diseases such as cancer, cardiovascular conditions, and neurological disorders significantly enhances treatment efficacy and survival rates. However, traditional diagnostic methods often suffer from limitations such as diagnostic errors, delayed results, and subjectivity. AI technologies, particularly machine learning (ML) and deep learning (DL), have demonstrated the ability to analyze large datasets, recognize patterns, and predict outcomes with greater accuracy and speed than conventional methods. This study aims to explore the impact of AI on early disease detection, focusing on its applications in diagnostic medicine. The research employs a systematic review of AI-based diagnostic tools and their clinical performance across various diseases. Data from peer-reviewed journals and clinical trials are analyzed to assess the accuracy, efficiency, and clinical implementation of AI technologies. The findings reveal that AI has the potential to significantly improve diagnostic accuracy, reduce diagnostic errors, and expedite disease detection, particularly in resource-limited settings. However, challenges remain regarding data privacy, algorithm transparency, and integration into clinical practice. In conclusion, AI stands poised to transform early disease detection, but careful consideration of ethical and technical challenges is essential for its widespread adoption.